Activin is a neural inducer of a male-specific muscle in Drosophila. - Kimura, K.I.; Kumano, R.; Yamamoto, D. (Scientific reports, 2024)
Drosophila melanogaster has a pair of male-specific muscles called the muscle of Lawrence (MOL) in abdominal segment 5 (A5) of adult flies. The MOL is produced only when its innervating motoneuron expresses FruitlessM (FruM) neural masculinizing proteins. We show that MOL induction is hampered by: (1) silencing electrical activities in the motoneuron, (2) blocking vesicular release from the motoneuron, and (3) knocking down Activin ß (Actß) in the motoneuron or knocking down Actß signaling pathway components in the myoblasts. Our timelapse live imaging of the developing neuromuscular system reveals that, upon contact with the presumptive MOL, the motoneuronal axon retracts concomitant with the progression of MOL degeneration resulting from neural silencing. We conclude that MOL formation depends on the bidirectional trophic interactions between pre- and postsynaptic cells, with motoneuron-derived Actß playing an inducing role in MOL formation.